Pruritus bei systemischen Erkrankungen - Kremer, Andreas; Mettang, T. (Internist, 2019)
Chronic pruritus is a symptom of various internal disorders. In contrast to dermatological diseases, pruritus does not present with primary skin alterations in these patients. However, intense scratching my cause secondary skin changes such as abrasion, excoriation, prurigo nodularis, or in rare cases even scarring. The most common internal causes for chronic pruritus are chronic kidney disease, hepatobiliary, and hematological disorders as well as adverse drug reactions. Pruritus is less commonly seen in patients with endocrine or metabolic diseases, malabsorption syndromes, infectious diseases, and solid tumors. The pathogenesis of pruritus in these disorders remains largely elusive, albeit first insights have been gained for uremic and cholestatic pruritus. Antipruritic treatment is therefore symptomatic in most cases and may represent a clinical challenge. The calcium channel blockers gabapentin and pregabalin have the best proven efficacy in chronic kidney disease associated pruritus. In Japan, nalfurafine, a κ-opioid receptor agonist, has been licensed for this indication. UVB light may also attenuate uremic symptoms. In patients suffering from hepatobiliary disorders the sequestrant cholestyramine and the enzyme inducer rifampicin are effective. Furthermore, bezafibrate, the μ‑opioid receptor antagonists and, in Japan, nalfurafine may be used to ameliorate cholestatic pruritus. So far, no randomized controlled trials have been performed for chronic itch in other internal disorders. Antipruritic treatment is symptom-based with a focus on the effective therapy of the underlying disease.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Antipruritics; Cholestasis; Itching; Lymphoma; Renal insufficiency; chronic